Anesthetic Efficiency of 2-Phenoxyethanol on Broodstock of Salmo munzuricus, a New Trout Species Originating from Munzur Stream - Can, Erkan; Basusta, Asiye; Karatas, Bilal (Kafkas Univ, Veteriner Fakultesi Dergisi, 2018)
Salmo munzuricus is a newly-named species of trout that spreads through rivers flowing along the Munzur Valley National Park. The efficacy of anaesthetic 2-phenoxyethanol was evaluated in indigenous brown trout in the present study. Fish were divided into three weight classes: 100-200 g W1), 200-400 g W2) and 400-600 g W3) and they were exposed to four concentrations of anaesthetic 0.2, 0.3, 0.4 and 0.5 mL L-1). The lowest induction time was identified in the group W3 while the highest one was in the group W1. The lowest recovery time occurred after 73.2 +/- 3.83 sec in the group W3 and the highest one was 136 +/- 31.46 sec in the group W1. The recovery times were increased with increasing the concentration of 2-phenoxyethanol in the group W1. However, recovery times in the groups W2 and W3 were significantly longer than observed in W1, generally. Besides, it was indicated that fish size affected induction times and recovery times. As a result of the present study, the most appropriate concentrations were determined as 0.4 mL L-1 at weights of 100-400 g while 0.5 mL L-1 at weights of 400-600 g for 2-phenoxyethanol in Salmo munzuricus broodstock.
Munzur akarsuyu orijinli yeni bir alabalık türü olan salmo munzuricus’un anaç bireyleri üzerinde 2-fenoksietanol’ün anestezik etkinliği
Keywords: Fish anesthesia; Recovery; Brown trout; Salmo munzuricus; Broodstock; 2-phenoxyethanol; Anesthetic; Effective concentration; Fish size